2016
DOI: 10.1007/s12032-016-0803-3
|View full text |Cite
|
Sign up to set email alerts
|

Plasma cell maturity as a predictor of prognosis in multiple myeloma

Abstract: In this study, the impact of plasma cell maturity on the prognoses of multiple myeloma (MM) patients in the era of novel agents was investigated. Myeloma cell maturity was classified via immunophenotyping: myeloma cells showing mature plasma cell 1 (MPC-1)-positive and CD49e-positive cells were considered mature type; MPC-1-positive and CD49e-negative cells were considered intermediate type; and MPC-1-negative cells were considered immature type. This study included 87 newly diagnosed MM patients who were init… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 31 publications
1
11
0
Order By: Relevance
“…This observation is consistent with the fact that the patients included in our study received a treatment regimen that contained lenalidomide, a thalidomide-like drug. On the other hand, we have shown that DEPTOR induces PC maturation, and it has been reported that the maturation of myeloma cells is associated with sensitivity to anti-myeloma agents [30, 34, 4547], including lenalidomide [45]. In fact, plasma cell maturity seems to be an indicator of good prognosis in MM [47].…”
Section: Discussionmentioning
confidence: 83%
“…This observation is consistent with the fact that the patients included in our study received a treatment regimen that contained lenalidomide, a thalidomide-like drug. On the other hand, we have shown that DEPTOR induces PC maturation, and it has been reported that the maturation of myeloma cells is associated with sensitivity to anti-myeloma agents [30, 34, 4547], including lenalidomide [45]. In fact, plasma cell maturity seems to be an indicator of good prognosis in MM [47].…”
Section: Discussionmentioning
confidence: 83%
“…Interestingly, both γSI and Sirtinol had also a potent effect on the expression of the maturation antigen CD49e (Fig. 5 ) that is a differentiation agent for MM cells and is associated with a better prognosis of MM patients 46 . Notably, miR-34a transfection caused a rebound/protective effect in MM cells with a strong reduction of CD49e expression that was however completely counteracted by both γSI and Sirtinol treatment, with even a final potentiation of antigen expression.…”
Section: Discussionmentioning
confidence: 96%
“…The close relationship between Cdc37 and Xbp1s led us to ask whether Cdc37 also functions in plasma cell differentiation and maturation. We found that knockdown of Cdc37 by shRNA resulted in decreased secretion of Ig light chain and repressed expression of plasma cell maturation markers, such as Xbp1s, CD38, and CD49e 27,28 in NCI-H929 cells (Fig. 4a) and KMS11 cells (Fig.…”
Section: Suppression Of Cdc37 Induces Immaturity Of Plasma Cellsmentioning
confidence: 91%